Changes in human immunodeficiency virus and sexually transmitted infections-related sexual risk taking among young Croatian adults: 2005 and 2010 population-based surveys - Landripet, Ivan; Štulhofer, Aleksandar; Baćak, Valerio (2011)
Aim. To determine changes in sexual behaviors and other relevant characteristics related to human immunodeficiency virus (HIV) and sexually transmitted infection (STI) risks among young Croatian adults. Method. We surveyed adults aged 18-24 in 2005 (n = 1092) and 18-25 in 2010 (n = 1005). Both samples were probabilistic and stratified by county, settlement size, age, and gender. The samples were non-matched. Trained interviewers conducted structured face-to-face interviews in participants’ households. The part of the questionnaire assessing sensitive information was self-administered. Results. A majority of participants at both survey points (85.2%-86.2%) were sexually active. Median age at sexual debut (17 years) remained unchanged. Lifetime number of sexual partners was also stable. More women than men reported only one lifetime sexual partner. The prevalence of condom use at first intercourse increased (from 62.6 to 70%, P = 0.002), while the prevalence of condom use at most recent sexual intercourse remained stable (54% in 2005 and 54.7% in 2010). Consistent condom use also remained unchanged. Consistent condom use in the past year was reported by 19.2% participants in 2005 nad 20% in 2010.. At both survey points for both genders, consistent condom use was associated with age (odds ratio [OR] W2005 = 0.74, P = 0.004 ; ORW2010 = 0.72, P < 0.001 ; ORM2005 = 0.73, P < 0.001 ; ORM2010 = 0.80, P = 0.006), negative attitudes toward condom use (ORW2005 = 0.84, P = 0.001 ; ORW2010 = 0.90, P = 0.026 ; ORM2005 = 0.92, P = 0.032 ; ORM2010 = 0.90, P = 0.011)), and condom use at first intercourse (ORW2005 = 3.87, P < 0.001 ; ORW2010 = 4.64, P < 0.001 ; ORM2005 = 5.85, P < 0.001 ; ORM2010 = 4.03, P < 0.001). In the observed period, HIV/AIDS knowledge was stable. Conclusion. Risky sexual practices remain common among young Croatian adults. Given the recently reported STI prevalence rates in this age cohort, introduction of school-based sex education that would focus on protective behavioral and communication skills seems to be of crucial epidemiological importance.
Projekt MZOS
ENG